HUBUNGAN INTENSITAS BERMAIN GAME ONLINE TERHADAP MOTIVASI BELAJAR SISWA KELAS V SD 2 KARANG BENER - Muzdalifah, Muzdalifah; Roja, Vebby Meilia; Maharani , Fara Fatika; Niklah, Wardatutsani Latifun; Ardianti, Sekar Dwi; Ismaya, Erick Aditia (Program Studi PGSD, FKIP, Universitas Mataram, 2024)
ABSTRACK This research aims to determine the relationship between the intensity of playing online games and the learning motivation of class V students at SD 2 Karang Bener, Kudus Regency. The correlation method is the method used in this research using a quantitative correlation approach. The population in this study was all class V students at SD 2 Karang Bener, totaling 8 students. The samples taken were all fifth grade students at SD 2 Karang Bener, because the population was less than 10 students. The data collection method used was a questionnaire. The questionnaires used were online game playing intensity questionnaires and learning motivation questionnaires consisting of 10 question items. Results based on the Rank Spearman correlation statistical test of the relationship between the intensity of playing online games and learning motivation showed that the Spearman Rank correlation test I results obtained a Correlation Coefficient value of 0.291, meaning the correlation between the two variables was very weak and a significance value of 0.484 (p>0.05) was obtained. Because the p-value is > 0.05, the test decision is that Ho is accepted and HÎ± is rejected. So it was concluded that there was no relationship between the intensity of playing online games and the learning motivation of SD 2 Karang Bener students. Conclusions based on these results are expected for teachers and parents to pay more attention to their children, especially including children's activities in using technology, which is currently developing increasingly rapidly, especially in generating student motivation and achievement through technological developments.